Atentado à formação de um Espirit de Corps: pelas tentativas da administração gerencial por um discurso da eficiência e pelas tentações dos 'Espíritos de Porco': o curso de formação dos especialistas em políticas públicas e gestão governamental - Silva, Adélia Cristina Zimbrão da (2001)
This dissertation discuss the course of formation of EPPGG' (Specialists on Public Politics and Administration). We did a brief historical research on the origins of this career, stressing the problems of its implementation. We describe the process of selection and formation of 'EPPGG' classes, focusing our attention on the first and fifth classes, the latter being the main object of our study. We avoided the standard approaches to this suject and based our investigation on the daily social interaction developed during the course, trying to unveil conflicts that show internal problems of the career and of 'ENAP' (Scholl of Public Administration).